PENGARUH DOMPET DIGITAL DAN RELIGIUSITAS TERHADAP MENTAL ACCOUNTING PADA FAMILY WELFARE - Ardhi, Qisthi; Tungga Dewi, V.Ananta Wikrama; Sulastri, Rini (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2024)
The development of technology, particularly the use of e-money, is something that cannot be avoided. Digital wallets are used by all segments of society across many service and goods providers. Of course, the use of digital wallets and financial decisions must be made carefully. Therefore, the concept of mental accounting can help determine spending decisions to meet needs, especially household needs. Religion serves as a guide in daily life. Thus, the level of religiosity can influence the scale of spending decisions within households. The aim of this study is to examine the impact of digital wallets and religiosity on mental accounting concerning family welfare. This research employs reliability tests, validity tests, classical assumption tests, and multiple regression tests. Religiosity influences mental accounting. Individuals with strong religious beliefs tend to manage their finances more wisely. Their financial decisions will be made in accordance with sound religious teachings. Digital wallets do not have an impact on mental accounting.